Aktualisasi Pendampingan Foto Produk Sebagai Media Promosi Online UMKM ‘Jamu Gendong Kiringan' Di Masa Pandemi Covid-19 - Fadhilah Salsabila; Muhammad Eko Atmojo (Parabela: Jurnal Ilmu Pemerintahan & Politik Lokal, 2022)
The purpose of this study is to analyze the policies implemented by the Bantul Regency Government in conducting online promotion of MSMEs during COVID-19. The presence of the COVID-19 pandemic has triggered market difficulties for MSMEs, as happened in the Gendong Kringan Herbal Tourism Village in Bantul Regency, DIY. This study uses a qualitative descriptive method, with indicators of communication size, resources, disposition, and bureaucratic structure. Communication is very well established and coordinated between the parties involved. Communication is carried out by coordinating several segments such as the photographer community, the Bantul Tourism Office, the Jamu Gendong Kiran Manager to the community of the Jamu Gendong Kiringan tourist village. The availability of resources that include human resources, budget, and infrastructure is sufficient to support product photo shooting activities in the Gendong Kiran Herbal Tourism Village. the disposition/attitude government is very enthusiastic about introducing these tourist village destinations. This is evident in terms of the commitment shown by the Bantul Tourism Office is very high. the bureaucratic structure in product photo assistance activities is carried out by the division of each task and can be carried out properly.